Fast, fully automated global and local magnetic field optimization for fMRI of the human brain. - Wilson, J; Jenkinson, M; de Araujo, I; Kringelbach, M; Rolls, E; Jezzard, P (2002)
The aim of this novel technique is to allow researchers, particularly those operating at high static magnetic field strengths on fMRI applications, to tailor the static magnetic field within the brain. The optimum solution for their experimental needs is reached, utilizing the full potential of the active shims at their disposal. The method for shimming human brain, which incorporates automatic brain segmentation to remove nonbrain tissue from the optimization routine, is presented and validated. The technique is fast, robust, and accurate, achieving the global minimum to a static field homogeneity function of the in vivo brain. Both global and specified local regions of the brain can be selected on which to optimize the shims without requiring skilled intervention. The effectiveness of the automated local shim is demonstrated in an olfactory fMRI study where significant activations in the orbitofrontal cortex were very clear when the above method was employed.